i have an algebraic expression to evaluate =
8x+9y-(2x+y)
x=4 and y =6
this is how im doing it
step 1 : 8x+9y -8x+ (-6y)
answer book states answer is 72 how is that im suppose to get that number
im severely confused as to what im doing wrong
i have an algebraic expression to evaluate =
8x+9y-(2x+y)
x=4 and y =6
this is how im doing it
step 1 : 8x+9y -8x+ (-6y)
answer book states answer is 72 how is that im suppose to get that number
im severely confused as to what im doing wrong
We have not turned the -2x into -8x.We have put 4 in -2x=-2*4=-8
-y=-6.
so we get answer 72.
trigonometry